Colloidal chemistry with patchy silica nanoparticles - Rouet, Pierre-Etienne; Chomette, Cyril; Adumeau, Laurent; Duguet, Etienne; Ravaine, Serge (Beilstein Journal of Nanotechnology, 2018)
We report a new route to synthesize clusters, or so-called colloidal molecules (CMs), which mimic the symmetry of molecular structures made of one central atom. We couple site-specifically functionalized patchy nanoparticles, i.e., valence-endowed colloidal atoms (CAs), with complementary nanospheres through amide bonds. By analogy with the Gillespie formalism, we show that AX4, AX3E1 and AX2E2 CMs can be obtained from tetravalent sp3-like CAs when the relative amount of both building units is varied in a controlled manner. We obtain AX2 CMs from divalent sp-like CAs. We also show that it is possible to covalently attach two different types of satellites to the same central patchy nanoparticle to create more complex CMs, opening the way to the fabrication of new multifunctional nanostructures with well-controlled shape and composition.
Keywords: colloidal molecules; covalent bonding; patchy nanoparticles; valence